Alterations of Renal Function in Patients with Diabetic Kidney Disease: A BOLD and DTI Study. (30th September 2022) - Wei, Xiaobao; Hu, Runyue; Zhou, Xiaoli; Ni, Lihua; Zha, Dongqing; Feng, Huiling; Xu, Haibo; Wu, Xiaoyan
Abstract : Objectives . Our study aims to determine the patterns of renal oxygenation changes and microstructural changes by BOLD and DTI with deteriorating kidney function in patients with diabetic kidney disease (DKD). Methods . Seventy-two patients with type 2 diabetes mellitus (DM) and twenty healthy controls (HCs) underwent laboratory examinations, and renal BOLD and DTI images were obtained on a 3T-MRI machine. R 2 ∗, fractional anisotropy (FA), and average diffusion coefficient (ADC) values were evaluated. DM patients were divided into three subgroups (Group-DI/DII/DIII, based on urinary albumin-creatinine ratio (UACR)) and a nondiabetic kidney disease group (Group-NDKD). D-value and MCR of R 2 ∗ and FA were proposed to evaluate the differentiation between medulla and cortex of the individual kidney among HCs and three subgroups for reducing individual differences. Comparisons were made between NDKD and kidney function-matched DKD patients. Correlations between MRI parameters and renal clinical indices were analyzed. Results . Compared with Group-HC/DI, medullary R 2 ∗ and FA values were significantly different in Group-DII/III. The D-value of R 2 ∗ and FA in Group-III were significantly smaller than that in Group-HC. However, only MCR of R 2 ∗ in Group-III was significantly smaller than that in HCs. Medullary R 2 ∗ and FA were negatively associated with serum creatinine (SCr) and cystatin C (Cys C) and positively associated with eGFR. Conclusions . With renal function declining, BOLD and DTI could capture alterations including the first rising and then falling medullary R 2 ∗, continuously declining medullary FA, and apparent cortex-medullary differentiation in DKD patients. The MRI parameters showed renal changes accompanied by varying degrees of albuminuria, sharing common involvement in DKD and NDKD patients, but it was hard to distinguish between them. BOLD seemed more sensitive than DTI in identifying renal cortex-medullary differentiation.